Novel SSR4 gene splice variant leads to congenital disorder of glycosylation, type Iy - Li, Ning; Chen, Chen (Frontiers in Pediatrics, 2025)
BackgroundCongenital disorders of glycosylation (CDG) are a group of multi-systemic genetic disorders. Over 100 monogenic human diseases were known related with defects in glycosylation process. Defects of SSR4 gene lead to a rare X linked pattern of CDG which has been rarely reported.MethodWe reported a Chinese boy with developmental delay, microcephaly, and epileptic seizures. Whole exome sequencing and Sanger sequencing were performed in the family.ResultA novel maternal splice variant c.351+1del in SSR4 gene was identified by trio-exome sequencing, and confirmed by Sanger sequencing. The functional effect of the variant was further investigated by minigene. The minigene results showed three abnormal splice forms: (1) 1 bp deletion in 3′ end of exon 4; (2) 42 bp deletion in 3′ end of exon 4; (3) skipping of exon 4. All three forms resulted in truncated proteins. c.351+1del in SSR4 gene causes congenital disorder of glycosylation, type Iy, consisted with the proband's phenotype. Up to date, all of the pathogenic SSR4 gene variants were null variants. The most variants were reported in exon 4. Patients (within or between families) carrying the same variants exhibited phenotypic heterogeneity.ConclusionThe current study expanded the pathogenic variant spectrum of SSR4 gene and revealed the impact of c.351+1del on SSR4 splicing. Standardizing the transcript and naming conventions of variants were crucial for the study of SSR4 genotypes and phenotypes.